FAKTOR PENENTU PERAN SERTA PETANI DALAM MEMPERTAHANKAN KEBERLANJUTAN LUMBUNG PANGAN MASYARAKAT (LPM) - Johanna Suek; Hendrikus Lepa Sabaora; Made Tusan Surayasa; I Wayan Nampa (Buletin Ilmiah Impas, 2022)
The development of Community Food Estate is important to maintain the availability of food locally. The development of food estate is determined by the activeness of the famer groups and their members. The growth and development of food estate is observed through the participation of the farming community in managing them, starting from planning activities, organizing activities, implementing activities, using results, evaluating and monitoring. This study aims to examine the active status of farmers' participation in supporting the development of community food barns and describe various determinants of the active participation of farmers. The survey method was used to obtain information on 85 farmers randomly drawn from eight farmer groups. The findings show that 65% of farmers play a fairly active role with a score of 3.01. Significant determinants of farmer activity are the number of family members, dependency ratio, non-formal education of farmers, and farmer mothers, land area and rice equivalent production. Meanwhile, the determinants of formal education of farmers and peasant mothers did not show a significant influence.